2021
DOI: 10.1039/d1ra06594g
|View full text |Cite
|
Sign up to set email alerts
|

Li-doped beryllonitrene for enhanced carbon dioxide capture

Abstract: Lithium-doped beryllonitrene monolayer can effectively chemisorb carbon dioxide molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…These values agree well with the direct relationship between the magnitude of the charge density and electrocatalytic activities. In this study, we defined the charge density by ρ = Q / S , where ρ is the electron density of the adsorbent, Q is the total charge, and S = a × b × sinγ­( a and b are the optimized lattice constants and γ is the angle between the lattice vectors , ) is the surface area of the 4 × 4 supercell. According to Figure a, higher charge density improves the adsorption efficiency representing a smooth exponential curve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values agree well with the direct relationship between the magnitude of the charge density and electrocatalytic activities. In this study, we defined the charge density by ρ = Q / S , where ρ is the electron density of the adsorbent, Q is the total charge, and S = a × b × sinγ­( a and b are the optimized lattice constants and γ is the angle between the lattice vectors , ) is the surface area of the 4 × 4 supercell. According to Figure a, higher charge density improves the adsorption efficiency representing a smooth exponential curve.…”
Section: Resultsmentioning
confidence: 99%
“…It can react with different atoms and create an extensive variety of compounds and complexes, especially 2D beryllium allotropes. Moreover, Be, depending on the constituent elements and the growth conditions of the structure, was found to exhibit amphoteric behavior and change its coordination number. , All these attributes manifest the potential of beryllonitrene as an attractive medium for practical applications such as CO 2 capture and storage. However, the CO 2 adsorption energy on the pristine BeN 4 sheet, due to the different anchoring capability of N atoms leading to the lack of active adsorption sites for the molecule, is van der Waals type, a weak interaction. …”
Section: Introductionmentioning
confidence: 99%
“…The research conducted is very few regarding its potential uses, notably in gas sensing. For example., Li-doped BeN 4 for the capture of CO 2 was reported by Pu et al The pristine BeN 4 monolayer was incapable of CO 2 capturing due to low adsorption energy, but the Li doping could enhance it [39]. Similarly, Mahmoudi et al also showed that the vacancy created in the BeN 4 monolayer could modulate the CO 2 adsorption capability [40].…”
Section: Introductionmentioning
confidence: 88%
“…Because of its extraordinary stability and electrical conductivity capabilities, beryllonitrene is of interest in a variety of sectors, including materials science and electronics. This is because beryllium, which is lightweight, forms strong covalent bonds with nitrogen 36 .
Figure 1 Beryllonitrene sheet with unit cell 35 .
…”
Section: Topological Indices For Beryllonitrenementioning
confidence: 99%